Healthcare Work in Marriage: How Gay, Lesbian, and Heterosexual Spouses Encourage and Coerce Medical Care. (December 2018) - Reczek, Corinne; Gebhardt-Kram, Lauren; Kissling, Alexandra; Umberson, Debra
Marriage benefits health in part because spouses promote one another's well-being, yet how spouses facilitate formal healthcare (e.g., doctor's visits, emergency care) via what we call healthcare work is unknown. Moreover, like other aspects of the marital-health link, healthcare work dynamics likely vary by gender and couple type. To explore this possibility, we use in-depth interviews with 90 midlife gay, lesbian, and heterosexual spouses to examine how spouses perform healthcare work. Our results show that in heterosexual marriage, women perform the bulk of healthcare work and typically do so in coercive ways. A minority of heterosexual men provide instrumental healthcare work for their wives. Gay and lesbian spouses appear to commonly use both coercive and supportive healthcare work strategies to effectively promote healthcare use. Our findings demonstrate the ways spouses are central to supporting and coercing one another to obtain medical care and how these patterns are gendered.